The Optimization of Ecological and Economic Systems is on the Basis of the Antysypatyv Management (Economic journal of Lesya Ukrainka Volyn National University, 2015)
The author singled out the types of risks that affect to the ecological and economic systems of the enterprise. The author identified and analyzed the main directions and stages of the antysypatyv management of ecological and economic systems of the company
Keywords: the antysypatyv management, ecological and economic system of the enterprise, optimization, risks and threats